2016
DOI: 10.1159/000446395
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Activity-Dependent and Sensory Activity-Independent Properties of the Developing Rodent Trigeminal Principal Nucleus

Abstract: The whisker-sensory trigeminal central pathway of rodents is an established model for studies of activity-dependent neural plasticity. The first relay station of the pathway is the trigeminal principal nucleus (PrV), the ventral part of which receives sensory inputs mainly from the infraorbital branch of the maxillary trigeminal nerve (ION). Whisker-sensory afferents play an important role in the development of the morphological and physiological properties of PrV neurons. In neonates, deafferentation by ION t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…But their central axons in the brainstem are segregated into distinct domains called barrelettes, where they synapse on different postsynaptic neurons 38 . While molecular differences play a major role in topographically sorting the central axons of whisker-innervating sensory neurons in prenatal mice, sensory experience from the periphery refines the topographic organization and instructs point-to-point synaptic connections postnatally 50,51 . Sensory experience gives correlated activity to sensory neurons innervating the same whisker and directs their central axons to converge into the same circuit through the Hebbian mechanism, enabling “neurons that fire together to wire together” 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…But their central axons in the brainstem are segregated into distinct domains called barrelettes, where they synapse on different postsynaptic neurons 38 . While molecular differences play a major role in topographically sorting the central axons of whisker-innervating sensory neurons in prenatal mice, sensory experience from the periphery refines the topographic organization and instructs point-to-point synaptic connections postnatally 50,51 . Sensory experience gives correlated activity to sensory neurons innervating the same whisker and directs their central axons to converge into the same circuit through the Hebbian mechanism, enabling “neurons that fire together to wire together” 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for the vPrV, a recent review identified and discussed activity-dependent and independent developmental features [27]. Several properties of the vPrV neurons develop independent of peripherally evoked activity.…”
Section: Tactile Nuclei Of the Brainstemmentioning
confidence: 99%